Observer variability in histopathological reporting of transitional cell carcinoma and epithelial dysplasia in bladders. Issue 1 (January 1990) - Robertson, A J; Beck, J S; Burnett, R A; Howatson, S R; Lee, F D; Lessells, A M; McLaren, K M; Moss, S M; Simpson, J G; Smith, G D
Abstract : Sections from 90 urinary bladder biopsy specimens were examined by 11 consultant histopathologists with varying experience to determine the appropriateness of existing pathology terminology. Analysis with kappa statistics showed fair to good agreement in the grading and staging of transitional cell carcinoma. There was also reasonable agreement in the diagnosis of high grade dysplasia in random biopsy specimens from the urothelium adjacent to the neoplasm, but very poor agreement for lesser degrees of dysplasia. It is concluded that the present classification of bladder carcinomata is reliable and that pathologists can determine stage with a high degree of reproducibility and grade with a fair degree of reproducibility.